Gene, Stem Cell, and Alternative Therapies for SCA 1 - Wagner, Jacob L.; O'Connor, Deirdre M.; Donsante, Anthony; Boulis, Nicholas M. (Frontiers in Molecular Neuroscience, 2016)
Spinocerebellar ataxia 1 is an autosomal dominant disease characterized by neurodegeneration and motor dysfunction. In disease pathogenesis, polyglutamine expansion within Ataxin-1, a gene involved in transcriptional repression, causes protein nuclear inclusions to form. Most notably, neuronal dysfunction presents in Purkinje cells. However, the effect of mutant Ataxin-1 is not entirely understood. Two mouse models are employed to represent spinocerebellar ataxia 1, a B05 transgenic model that specifically expresses mutant Ataxin-1 in Purkinje cells, and a Sca1 154Q/2Q model that inserts the polyglutamine expansion into the mouse Ataxin-1 locus so that the mutant Ataxin-1 is expressed in all cells that express Ataxin-1. This review aims to summarize and evaluate the wide variety of therapies proposed for spinocerebellar ataxia 1, specifically gene and stem cell therapies.